Implementation of 21st Century Learning in Sharia Economics Study Program - Kiswantoro Deddy; Shanty Shanty; Endang Komara (Edumaspul: Jurnal Pendidikan, 2023)
21st century education is expected to produce human resources who have critical, creative, communicative, and collaborative thinking skills. The education system in Indonesia must be able to adapt to equip students with the required competencies. One of the right steps taken to support the mastery of 21st century skills is to apply the Ethnopedagogy learning framework with the cultural character model of the Betawi Ethnic Door Cross Tradition. The purpose of the research in this article is twofold. 1. Examining the concept of Ethnopedagogy framework and learning model of Betawi Ethnic Door Cross Culture 2. Describe the application of 21st century learning through the framework of Ethnopedagogy with the Betawi Ethnic Door Cross Cultural model. The research method used is qualitative method. Data collection techniques use observation, documentation, and interviews. The results of the research in this article are the application of 21st century learning through the framework of the Betawi Ethnic Door Cross Culture with the method of reciprocating rhymes, the application of reciprocating rhymes in learning based on local wisdom in the Sharia Economics Study Program of STAI Shalahudin Al Ayuubi Jakarta is used as one of the alternative learning in the 21st century recommended in the material of oral pantun as an effort to introduce and preserve the nation's culture. This is because students are more motivated in participating in learning activities and are actively involved in planning, preparing rhyme card media, and implementing reciprocating rhyme activities.